Protest on the Roads an Analytical Study in The Light of Quran and Sunnah - Hafeez Arshad Hashmi; Qammar Aziz; Munir Subhani; Prof Dr. Abdul Wahab; Prof Dr. Fazal Ilahi Khan; Prof Dr. Muhammad Aslam (Al-Qanṭara, 2022)
ABSTRACT Any country's progress and stability depends on its attachment with ideology, on its social, financial, political and defensive circumstances. If that state stands on its basic ideology and national aim, is saved from its internal and external chaos, is traveling on its way of financial development, justice prevails in it, a relation of love and trust exists between public and govt. ,and a whole set up for the spiritual and material needs of its inhabitants is there, then that state is built on solid and concrete grounds. There is no threat to its solidarity and wholeness and that state travels on the road of progress and development by being attached to its national goal. If we review our country's circumstances in the light of this standard then conditions seem contrary to this. In fact, we have become victim of financial poverty, political indiscipline, interior and exterior instability and moral disorder after getting detached from country's ideology and national goal. We have exposed our country's stability to threats by weakening its bases. Everywhere, there are lingual, racial and regional prejudices and war of rights is in progress on these bases. Amidst of this collective sin, hell of bloodshed, disturbance and deteriorative peace has occupied the country. Terrorism has become a matter of routine and has destroyed the peace of whole nation due to poor law and order conditions. Due to poor financial conditions, every child of the country is under the severe burden of debts. Financial development has halted due to unlawfulness and political instability. Nation is divided into different groups. Unity and harmony is absent whereas anti-Islam forces are busy in making their mutual differences prominent and making them quarrel with each other. Decline of moral values has hollowed the basis of society. In fact we too are responsible for bringing the country to this situation and this destruction is the result of our own habits and ignorance. We have become an example of what Quran says... یخربون بیوتھم بایدیھم[i]۔ They destroyed their homes References [i] Al Quran, Alhashar, 59:2.